Host-adapted metabolism and its regulation in Bacterial Pathogens (2015)
Pathogens adapt their metabolism rapidly to the host. Our topic covers these phenomenon regarding extracellular and intracellular pathogens as well as general methods to elucidate different metabolic adaptation processes - an essential guide for any scientist wanting to keep abreast of recent developments in infection biology.